Promoting Global Awareness in Second Grade Students - Fran Wilson; Nicole Prater; Kristy Wanstrath; Tammy Saunders (WOW Stories, 2012)
The Madeira Literacy Community developed plans and strategies to accomplish their goal for the school year: promote global awareness among the students. Critical steps to accomplishing this goal were selecting quality children's literature to read aloud, and to use this global literature in cross-curricular instruction. This vignette focuses on what books were selected, how they were used, and the importance of critical discussion and student conversation.